Age of menarche and near adult height after long-term gonadotropin-releasing hormone agonist treatment in girls with central precocious puberty - Joon-Woo Baek; Hyo-Kyoung Nam; Dahee Jin; Yeon Joung Oh; Young-Jun Rhie; Kee-Hyoung Lee (Korean Society of Pediatric Endocrinology, 2014)
PurposeGonadotropin-releasing hormone agonist (GnRHa) is known for improving final adult height in patients with central precocious puberty (CPP). This study aimed to investigate the age of menarche and near adult height in girls with CPP who had been treated with GnRHa.MethodsIn this retrospective study, we reviewed the medical records of 71 Korean girls with CPP who had started menarche or reached over 13 years of bone age after long-term GnRHa treatment. We estimated near adult height using the Bayley-Pinneau method and identified the age of menarche in girls with CPP.ResultsMean chronological and bone age at menarche were 11.9±0.7 and 12.8±0.4 years, respectively. The period between menarche and the end of treatment was 14.0±5.6 months. Posttreatment near adult height was 163.8±4.7 cm, which was significantly greater than pretreatment predicted adult height (158.7±4.1 cm).ConclusionGnRHa treatment in girls with CPP could improve final adult height and made the age of menarche close to that of the general population.